Regenerating hair cells in vestibular sensory epithelia from humans - Ruth Rebecca Taylor; Anastasia Filia; Ursula Paredes; Yukako Asai; Jeffrey R Holt; Michael Lovett; Andrew Forge (eLife, 2018)
Human vestibular sensory epithelia in explant culture were incubated in gentamicin to ablate hair cells. Subsequent transduction of supporting cells with ATOH1 using an Ad-2 viral vector resulted in generation of highly significant numbers of cells expressing the hair cell marker protein myosin VIIa. Cells expressing myosin VIIa were also generated after blocking the Notch signalling pathway with TAPI-1 but less efficiently. Transcriptomic analysis following ATOH1 transduction confirmed up-regulation of 335 putative hair cell marker genes, including several downstream targets of ATOH1. Morphological analysis revealed numerous cells bearing dense clusters of microvilli at the apical surfaces which showed some hair cell-like characteristics confirming a degree of conversion of supporting cells. However, no cells bore organised hair bundles and several expected hair cell markers genes were not expressed suggesting incomplete differentiation. Nevertheless, the results show a potential to induce conversion of supporting cells in the vestibular sensory tissues of humans.